2011
DOI: 10.1176/appi.ap.35.6.404
|View full text |Cite
|
Sign up to set email alerts
|

Burden and Stress Among Psychiatry Residents and Psychiatric Healthcare Providers

Abstract: Psychiatric residents in this study suffered higher levels of job burden and stress than other healthcare professionals, suggesting the need for changes in residency programs to deal with this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Data from other part of the globe also suggest that psychiatry residency is associated with a significant level of stress, emotional problems, poor sleep quality, burden, and burnt out. [ 15 16 17 ] However, an important fact to note was that higher level of stress was reported by trainees from premier institutes, suggesting that higher level of stress is associated with better training outcome and perception of competence by the trainee at the end of the training and later. This suggests that there is a need to develop training programs with optimal level of stress, without compromising on quality of training.…”
Section: Discussionmentioning
confidence: 99%
“…Data from other part of the globe also suggest that psychiatry residency is associated with a significant level of stress, emotional problems, poor sleep quality, burden, and burnt out. [ 15 16 17 ] However, an important fact to note was that higher level of stress was reported by trainees from premier institutes, suggesting that higher level of stress is associated with better training outcome and perception of competence by the trainee at the end of the training and later. This suggests that there is a need to develop training programs with optimal level of stress, without compromising on quality of training.…”
Section: Discussionmentioning
confidence: 99%
“…The 2013 Beyond Blue National Mental Health Survey of Doctors and Medical Students 6 suggested that the level of stress, distress, depression and suicide was higher in doctors compared with the general population and other professionals, particularly for students, residents and young and female doctors, indicating a particular duty of care to these groups. Psychiatry trainees suffer higher levels of job stress than other healthcare professionals and this may lead to burn-out, cynicism, and negative impacts on personal life.…”
Section: A ‘Right Brain’ Education – Principles and Considerationsmentioning
confidence: 99%
“…Intense, unprocessed affects may lead to burn out, poor morale and absenteeism, secondary traumatization, and defensive attitudes to patient care. 11 Psychiatrists have been shown to suffer higher levels of job stress than other healthcare professionals; 12 therefore the recommendation that one should be empathic may also have workplace health and safety implications.…”
Section: Costs and Benefits Of Empathymentioning
confidence: 99%